Nutritional and Biochemical Quality of Fresh and Cold-Smoked Rudd (Scardinius erythrophthalmus) Fillets during Refrigerated Storage - BOUZGARROU, Olfa; SADOK, Saloua (INSTM Bulletin : Marine and Freshwater Sciences, 2026)
Biochemicals and nutritional parameters of fresh and cold-smoked fillets of freshwater rudd (Scardinius erythrophtalmus) during refrigerated storage were investigated. Based on biochemical analysis, several indices were used to monitor the product quality over 9 weeks of refrigerated storage at 2±1°C. The results revealed the highest value for moisture and the lowest values for ASH content, carbohydrate, lipids, total volatile basic nitrogen (TVB-N) content, trimethylamine (TMA-N), and thiobarbituric acid concentrations (TBARS) in fresh fillets. During refrigerated storage, the results showed that an increase in microbial load was accompanied by a concomitant rise in volatile basic nitrogen (TVB-N), trimethylamine (TMA-N), and thiobarbituric acid concentrations (TBARS). However, these values were much lower than the acceptable limits for smoked fish products. Microbiological analysis indicated that cold-smoked rudd fillets had a shelf life of up to 9 weeks of refrigerated storage. Low levels of biogenic amines (BAs) were observed in fresh and smoked fillets throughout the entire storage period, with the exception of agmatine. The indices of atherogenicity (IA) and thrombogenicity (IT), with values of 1.54 and 1.59, respectively, did not show a significant change during 35 days of storage. These results showed that the cold smoking treatment led to an extension of the shelf life of the smoked net of the rudd up to 63 days of the refrigerated storage and presents potential advantages for the processing industry.